2022
DOI: 10.1186/s13012-021-01176-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-review of implementation determinants for policies promoting healthy diet and physically active lifestyle: application of the Consolidated Framework for Implementation Research

Abstract: Background Although multiple systematic reviews indicate that various determinants (barriers and facilitators) occur in the implementation processes of policies promoting healthy diet, physical activity (PA), and sedentary behavior (SB) reduction, the overarching synthesis of such reviews is missing. Applying the Consolidated Framework for Implementation Research (CFIR), this meta-review aims to (1) identify determinants that were systematically indicated as occurring during the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 73 publications
(107 reference statements)
1
24
0
Order By: Relevance
“… 23 PEN findings regarding implementation processes identified the following implementation barriers and facilitators as most important: cost, networking with other organizations/communities, external policies, structural characteristics of the setting, implementation climate, readiness for implementation and knowledge/beliefs of involved individuals. 24 We also found that knowledge on how certain policies are actually implemented, for instance the implementation of a sugar tax, is limited.…”
Section: Results: the Final System-based Pen Frameworkmentioning
confidence: 91%
“… 23 PEN findings regarding implementation processes identified the following implementation barriers and facilitators as most important: cost, networking with other organizations/communities, external policies, structural characteristics of the setting, implementation climate, readiness for implementation and knowledge/beliefs of involved individuals. 24 We also found that knowledge on how certain policies are actually implemented, for instance the implementation of a sugar tax, is limited.…”
Section: Results: the Final System-based Pen Frameworkmentioning
confidence: 91%
“…We used broad theoretical underpinnings to develop the data collection; however, no framework in particular was used to provide guidance, as none really fit. Our study indicates that the work to combine public policy concepts and implementation research frameworks has been initiated and should be continued in the future to inform data collection and increase the comparability of the reported data [21,76,77].…”
Section: Limitationsmentioning
confidence: 92%
“…There are issues this review could not and would not answer, but future research should address. It is important to quantify the influencing factors (92,96), and to analyze which influencing factors are interconnected. It is essential to analyze the factors that have an influence on implementation outcomes (97)(98)(99) and on health outcomes (100).…”
Section: Methodological Considerations-for Researchermentioning
confidence: 99%